Some Common Fixed Point Theorems in N-Fuzzy Metric Spaces with Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we prove some common fixed point theorems in newly defined space N-fuzzy metric space [8]. Our results generalize and extend the results of Mahmoud Bousselsal and Mohamed Laid Kadri [M. Bousselsal and M.L. Kadri, [1] A common fixed point theorem in fuzzy metric spaces